Business Feasibility Analysis of Freshwater Pomfret (Colossoma macropomum) Enlargement in Cages in Penyasawan Village Kampar Regency Riau Province - Rizki, Hafizri Deni; Hendrik, Hendrik; Arief, Hazmi (Jurnal Perikanan dan Kelautan, 2023)
This research was carried out in Penyasawan Village on 28 March – 28 April 2022. This study aims to analyze the investment, total costs, income, profits, feasibility, and business prospects of freshwater pomfret enlargement in cages in Penyesawan Village. The method used in this study is a survey method with 32 respondents as freshwater pomfret cultivators. The analysis used in this research is business analysis. There are two sizes of cages cultivated by farmers, namely small cages (8×3×2 m) and large cages (10×3×2 m). The results showed that for small cages, the investment of IDR60.531.480/year, the total cost is IDR115.775.107/year, the income is IDR179.874.000/year, and the profit is Rp64.098.893/year. For large cages, the investment is IDR80.223.080/year, the total cost is IDR157.065.240/year, the income is IDR246.834.000/year, and the profit is IDR89.768.760/year. Based on business feasibility, large cages are more feasible than small cages. Based on the prospects, this business is good in terms of profit, marketing, and environmental carrying capacity